2015
DOI: 10.1016/j.stem.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Seq with Waterfall Reveals Molecular Cascades underlying Adult Neurogenesis

Abstract: Somatic stem cells contribute to tissue ontogenesis, homeostasis, and regeneration through sequential processes. Systematic molecular analysis of stem cell behavior is challenging because classic approaches cannot resolve cellular heterogeneity or capture developmental dynamics. Here we provide a comprehensive resource of single-cell transcriptomes of adult hippocampal quiescent neural stem cells (qNSCs) and their immediate progeny. We further developed Waterfall, a bioinformatic pipeline, to statistically qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
761
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 734 publications
(847 citation statements)
references
References 35 publications
60
761
1
1
Order By: Relevance
“…Single-cell RNA sequencing as well as subsequent electrophysiological analyses have recently shown that NGP RGL stem cells express functional glutamate receptors (ref. 57; but see also ref. 58 for contrast and ref.…”
Section: Discussionmentioning
confidence: 97%
“…Single-cell RNA sequencing as well as subsequent electrophysiological analyses have recently shown that NGP RGL stem cells express functional glutamate receptors (ref. 57; but see also ref. 58 for contrast and ref.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis is consistent with the previously described alterations in the cell cycle of aged NSPCs (Apostolopoulou et al., 2017; Daynac et al., 2014, 2016; Stoll et al., 2011). Dbx2 is part of a cohort of transcription factor genes that are enriched in quiescent NSPCs of the SGZ and SVZ and are downregulated in NSPCs actively engaged in cell proliferation and neurogenesis (Codega et al., 2014; Shin et al., 2015), thus suggesting that Dbx2 may negatively regulate NSPC proliferation in both adult neurogenic niches. Elevated Dbx2 expression in adult NSPCs also phenocopied several of the molecular effects of aging, including the altered expression of key genes such as Sox2 and p21 that are associated with proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that their gradual differentiation, through successive rounds of proliferation and often an intermediate progenitor state, could allow them to acquire the most appropriate metabolism slowly. Indeed, recent RNA-seq data revealed that adult NSCs start to change their metabolism when they become activated and enter cell cycle (Llorens-Bobadilla et al, 2015;Shin et al, 2015). Even the recent identification of NSCs turning into neurons in the adult zebrafish forebrain without any apparent division seems to occur rather slowly (Barbosa et al, 2015), over the course of weeks, which would allow time for metabolic transition.…”
Section: Peripheral Sensory Neuronsmentioning
confidence: 99%
“…For example, maintenance of progenitors requires de novo lipogenesis (Knobloch et al, 2013), while commitment and differentiation are associated with reduced expression of glycolytic genes (Llorens-Bobadilla et al, 2015;Shin et al, 2015). This in turn is influenced by the activity of mTOR (Amiri et al, 2012;Kim et al, 2009), a metabolic rheostat involved in the integration of nutrients and regulation of growth factor signalling (Mihaylova et al, 2014).…”
Section: Peripheral Sensory Neuronsmentioning
confidence: 99%